LA FACHADA PRINCIPAL DEL PALACIO EPISCOPAL DE MURCIA: UN CASO SINGULAR DE PINTURA MURAL AL EXTERIOR Y DE PROBLEMÁTICA CONSERVACIÓN - Santiago Godos, Victoria (Imafronte, 1997)
The Bishop’s Palace in Murcia is one of the few 18th century Spanish Baroque monuments which conserves in its principal facade mural paintings as ornamental decoration, together with, fine stone-sculptured motits. This characteristic as well as the size and architectural quality of the building make it one of !he most unique without doubt. The decorative paintings represent in each of !he adornings, a group of motifs that are similar and form a type of tapestry, framed by attractive mouldings and rocaille (Rococo ornament) that surround medallions and shields in the form of a horn-ofplenty with rocaille. The state of conservation that this facade presents is very poor since thepictorial elements as well as the stone ones are highiy deteriorated. The diagnosis of its state will be referred to in more detail, intending to highlight the necessity to contribute to a prompt and adequate restoration that such a noble facade deserves.